THE USE OF EDUCATIONAL TECHNOLOGY IN FORMATIVE ASSESSMENT TO PROVIDE EQUITY - Selimova Gulsana (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract This  article  explores  the  role  of  educational  technology  in  supporting  equal formative assessment practices. It examines how technology-based tools can improve the process of formative assessments; provide students with more flexibility in their learning, increase student engagement, and receive instant feedback. The article also discusses the benefits of personalized learning and differentiated assessments, as well as  the  advantages  of  real-time  data  collection  and  analysis.  Specific  examples  of formative assessment technologies are provided, highlighting their impact on teaching and learning.